The synthesis and spectral characterization of N,N-bis(2-{[(2-methyl-2- phenyl-1,3-dioxolan-4-yl)methyl] amino}ethyl)N?N?- dihydroxyethanediimidamide and its complexes - Canpolat, E.; Kaya, M.; Öztürk, Ö.F. (My University, 2004)
N,N-Bis(2-{[(2-methyl-2-phenyl-1,3-dioxolan-4-yl)methyl]amino}ethyl) N?,N?-dihydr oxyethanediimidamide (LH2) has been synthesized and its mononuclear complexes with Co2+, Ni2+, Cu2+, Zn2+ and Cd2+ ions have been obtained. The mononuclear complexes indicated that the metal ions are ligand coordinated through the two N atoms, as do most of the vic-dioximes. The authenticity of the ligands and their complexes have been established by IR, 1H- and 13C-NMR spectra, UV-Visible spectroscopy, elemental analyses and magnetic susceptibility measurements.
Keywords: Complexes; Dioximes; Synthesis of vic-dioxime complexes; Transition metals